Nutritional properties of Ogi powder and sensory perception of Ogi porridge made from synthetic provitamin A: Novel Maize genotypes - CGIAR Research Program on Maize (2021)
Maize 2 genotype had the highest vitamin A contribution; meet 18.3% of the vitamin A requirements in children while in adult males and females (>19 years), 6.2 and 7.7%, respectively.